APPROACHES OF EUROPEAN COUNTRIES’ EDUCATIONAL SYSTEMS DEVELOPMENT (Journal of Information Technologies in Education (ITE), 2012)
International documents which determine the development and introduction of information and communication technologies (ICT) and which influenced on forming of priority approaches in strategies of development of the European countries modern educational systems are analysed in the article. Based on the research, conducted by educational net EURYDICE it is presented the comparative analysis of the state of introduction of National ICT strategies in European countries educational systems; it is considered the monitoring process as well as financings and structures which are responsible for the process of realization of ICT strategies in the educational systems of countries of Europe.
Keywords: ICT strategy; information and communication technologies; international experience; systems of education